KANIKOSEN (KOBAYASHI TAKIJI) “BACAAN LIAR” TAHUN 1920-AN DALAM RENTANG SEJARAH JEPANG - Muhammad Reza Rustam (IZUMI, 2016)
This paper describes a dynamics proletarian literature and its relationship with Kanikosen   novel by Kobayashi Takiji, including; the institution, ideology, production, and figures associated to narration used by Marxism theory posed by the author as one of the Japan "wild literatures" in the 1920s. This paper aims to usher the readers to the narrative of the Japanese proletarian literature and illustrates the Japanese proletarian literary map development. The form of “wildness” obtained by author is a social class conflict in literary texts such as in the Kanikosen   story. Like an empirical reality, text construction, especially characterizations, background, and language style reflecting a dynamics of everyday social life. Intimidation, exploitation, deception, torture, suffering labor on one side and on the other side, the accumulation of profits, accumulating capital individually, and the arbitrariness of employers conducted by the owners of capital, reflected brightly by Kobayashi Takiji.